A New Vaccination Method Based on Phage NgoΦ6 and Its Phagemid Derivatives - Piekarowicz, Andrzej; Kłyż, Aneta; Stein, Daniel C. (Frontiers in Microbiology, 2022)
Phagemid particles based on the Neisseria gonorrhoeae filamentous phage NgoΦ6 incorporate host proteins into phage/phagemid particles. We demonstrate that the host proteins incorporated into these particles can be encoded by chromosomal genes of the host bacterium or from plasmids able to replicate as an autonomous entity in the phagemid host. Phagemid particles were prepared from three types of cells; Salmonella enterica ser. Thyphimurium (pBSKS::Φ6fm(ST) containing phagemid genome as an autonomous plasmid, Haemophilus influenzae Rd containing phagemid (pBSKS::Φ6fm(Hin) integrated into the chromosome and S. enterica ser. Thyphimurium (pMPMT6:: Φ6fm(ST) containing an additional plasmid, pE1 HCV, encoding the Hepatitis C virus envelope glycoprotein E1. Approximately 200 µg of purified phage particles were used to immunize rabbits. The phagemid particles prepared from these three strains all elicited large amount of IgG antibodies able that were able to recognized bacterial host cells and proteins, as determine by ELISA and FACs analysis. The amount of specific anti-S. enterica ser.Thyphimurium, anti- H. influenzae or anti- E1 HCV protein were 170 μg/ml for anti-Salmonella, 80 μg/ml for anti-H. influenzae and 65 μg/ml of anti-E1 HCV protein. Taken in toto, these data suggest that classical phage display methods have underestimated the potential for filamentous phage as a novel immunogen delivery system.